Methodological issues in psychosocial research in adolescent and young adult cancer populations - Kosir, U (Mary Ann Liebert, 2019)
Survival rates of childhood cancer dramatically increased over the past few decades. On the other hand, adolescents and young adults (AYA) see a slower improvement and might face more psychosocial difficulties when confronting cancer and its aftermath. AYA patients have unique needs due to the nature of their developmental period. There is a need to continue identifying the factors that make some AYA cancer patients and survivors more susceptible to psychological distress. In order to continue making progress and strengthen current theoretical models, we ought to consider some of the current methodological limitations in the field of AYA psychosocial oncology.